THE FACE OF EVIL : The Muslim Beard Representation in Hollywood Movies in Post 9/11 Attacks - MECHERI, Fatima Zohra (Journal of Human Sciences, 2020)
Islam has been one of the highly misunderstood religions in the world. Many non-Muslim societies have never welcomed Islam. To Many Americans, the geographical imaginings of Arabs and Muslims are grounded on perceptions inherited from the Classical Orientalism that was established in Europe as a system of knowledge during the 18th and 19th centuries. Since the end of the Second World War, Americans have ornamented the early European prejudicial representation of Arabs and Muslims through constructing and disseminating essentialized and derogatory perceptions of this distinctive social group as inferior, backward, and dangerous ‘Other’. Ever since the 9/11 attacks and the escalation of the war on terror, images that successfully linked the Muslim bodily and religious practices with violence and terror gained great ascendancy in American mainstream media, popular culture, and political rhetoric. Focusing on the scale of the Muslim body, the present article probes the American motion picture industry (mainly Hollywood) representation of Muslim beard as a symbol of difference and danger in movies released in the post 9/11 attacks. Specifically, it examines beards as a bodily practice that supplies information about Muslims and as a key element used to breathe life into the reel bad Arab character in Hollywood movies. By focusing on Hollywood movies representations of bearded Muslim men, the article reveals how men’s beards have been embedded in the discourse of fear, danger, and terror.